(untitled) (Bodhi Path, 2022)
Following the beginning of industrialization, the amount of waste generated by the entire population has severely kept on increasing along with the exploitation of natural resources. The process of Waste Management requires the treatment of Waste from its formation to its disposal. The issue of Waste remains a challenge for many developed and under developing countries to build sustainable habitats. In the present era, Waste Management has become a concern for the whole world as it poses a serious hazard for the entire humanity. As the population and urbanization are rapidly expanding the quantity and characteristics of waste is also changing. India generates 277 million tons of waste annually and 1.50 lakh metric tonnes daily(2016 estimates). Corporate social responsibility is an evolving concept for every nation, and there is not a single accepted definition of CSR.CSR squarely can be defined as an attempt by the big corporates to alleviate the suffering of humankind and work for the betterment and wellbeing of the entire society. The ‘responsibility in CSR shall not only provide a check on their activity (as is understood by most of the corporates) but they shall also take care whether their manufactured product in any way lead to the degradation of the Environment or not. In the context of CSR, it is essential to del deep into the Buddhist text ‘Chakkavattiisuttam’ which touches on the point “that the real standard of the living of a nation does not merely depend on the number of rich people rather it lies more on the number of people that are alleviated of poverty and social suffering”. This paper attempts to focus on society and the environment concerning nature and the responsibility of corporate mobs to treat their waste efficiently.